Co-creation and collaborative knowledge at the service of the citizens - Sanz-Martos, Sandra (Anuario ThinkEPI, 2018)
Co-creation is a social, active, and creative process, based on a collaboration between the members of an institution / organization (producers / employees) and the clients / users, generating value for the latter. It is a collaborative process to enhance the creative thinking of users and to generate innovative ideas. In this way, the services provided by the organization are aligned with the needs and requirements of the clients. The public institutions of some autonomous communities in Spain are applying co-creation strategies to improve the services they provide to the public, while at the same time favoring closeness and proximity.